2021
DOI: 10.1002/mp.14988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maximum likelihood and conventional PET scatter scaling methods for 18F‐FDG and 68Ga‐DOTATATE PET/CT

Abstract: Purpose We aim to quantify differences between a new maximum likelihood (ML) background scaling (MLBS) algorithm and two conventional scatter scaling methods for clinical PET/CT. A common source of reduced image quantification with conventional scatter corrections is attributed to erroneous scaling of the initial scatter estimate to match acquired scattered events in the sinogram. MLBS may have performance advantages over conventional methods by using all available data intersecting the subject. Methods A retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Our study showed a significant lower IDIF accuracy for the absolute scatter correction method compared to the relative scatter correction set as default. Our results are consistent with a previous study showing an underestimation of scatter using the absolute scatter correction method [ 29 ]. However, the absolute scatter correction method improved the precision of IDIF in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed a significant lower IDIF accuracy for the absolute scatter correction method compared to the relative scatter correction set as default. Our results are consistent with a previous study showing an underestimation of scatter using the absolute scatter correction method [ 29 ]. However, the absolute scatter correction method improved the precision of IDIF in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The relative method is the default technique implemented in clinical PET imaging because it compensates for multiple scatter and for scatter contributions, scaling the activity located outside the axial FOV. The higher contrast between normophysiological uptakes for [ 18 F]DPA-714 than for [ 18 F]FDG probably explains why differences were greater for the CF IDIF between the use of relative and absolute scatter correction for [ 18 F]DPA-714 compared to [ 18 F]FDG data, which is consistent with two previous studies [ 29 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, we used absolute scatter estimation for correcting counts from the patient. The method underestimates scatter from out of FOV [ 26 ], which may bias -map estimation at edge planes; increasing PET bias of extracardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate scatter originating from the patient alone, in (13) and in (19) , we utilized absolute scatter estimation [ 26 ]. In this approach, the current EM image reconstruction and attenuation image were fed into a 2D implementation of the SSS.…”
Section: Ethodsmentioning
confidence: 99%